2020
DOI: 10.1038/s41541-020-00253-9
|View full text |Cite
|
Sign up to set email alerts
|

A nanoparticle vaccine that targets neoantigen peptides to lymphoid tissues elicits robust antitumor T cell responses

Abstract: Cancer vaccines using synthetic long peptides (SLP) targeting tumor antigens have been tested in the clinic but the outcomes have been unimpressive, perhaps because these peptides elicit predominantly CD4+ T cell responses. We hypothesized that enhanced delivery of peptide antigens to, and uptake in, secondary lymphoid tissues should elicit more robust CD8+ and CD4+ T cell responses and improved anti-tumor responses. Here, we have designed SLP-containing cationic lipoplexes (SLP–Lpx) that improve delivery of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Follow-up immunotherapy with anti-CTLA4 antibody resulted in complete remission of gp70-negative CT26 tumors in all mice in this study ( 178 ). In an inducible lung adenocarcinoma mouse model, vaccination using the G12D KRAS mutations as neoantigens and a novel synthetic long peptide-containing cationic lipoplex-based delivery platform stimulated both CD4 + and CD8 + T cell response and suppressed tumor growth, while combination with checkpoint inhibitor furthered such suppression ( 179 ). Similarly, both CD4 + and CD8 + T cell response has been reported in recent clinical studies following neoantigen-specific vaccination, across multiple cancer types.…”
Section: Oncodriver-specific and Neoantigen-driven Cd4 + T Helper Immune Responsementioning
confidence: 99%
“…Follow-up immunotherapy with anti-CTLA4 antibody resulted in complete remission of gp70-negative CT26 tumors in all mice in this study ( 178 ). In an inducible lung adenocarcinoma mouse model, vaccination using the G12D KRAS mutations as neoantigens and a novel synthetic long peptide-containing cationic lipoplex-based delivery platform stimulated both CD4 + and CD8 + T cell response and suppressed tumor growth, while combination with checkpoint inhibitor furthered such suppression ( 179 ). Similarly, both CD4 + and CD8 + T cell response has been reported in recent clinical studies following neoantigen-specific vaccination, across multiple cancer types.…”
Section: Oncodriver-specific and Neoantigen-driven Cd4 + T Helper Immune Responsementioning
confidence: 99%
“…During the past decades, a large number of nanoparticle types have been developed to target DCs and induce cellular immune responses. Among these nanoparticles, cationic particles are of special interest, because they have shown to have superior immunostimulatory properties as compared to their neutral and anionic analogues and have proven to be potent inducers of antigen-specific T-cells [ 9 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Recent preclinical and clinical studies have shown that cationic nanoparticles offer clinically applicable vaccine formulation platforms [ 9 , 10 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The charge, size, surface molecules and delivery mechanism of liposomes are all tailorable – this feature allows a liposome to mimic the size and surface markers of a pathogen for example ( 96 , 97 ). As particulate systems can protect peptides from degradation and control their release, liposomes provide peptides greater access to the spleen and lymph nodes which contain a higher proportion of cross-presenting DCs ( 98 , 99 ). Upon internalisation, the liposome can continue to promote antigen cross-presentation by enabling its peptide cargo to escape from the lysosome into the cytosol, a key step in antigen cross-presentation and stimulation of a robust CD8 + T cell response ( 100 ).…”
Section: Peptide Vaccine Formulation and Drug Delivery Systemsmentioning
confidence: 99%
“…In a study that looked at mutant KRAS SLP-Liposomes, the use of KRAS G12 mutant SLPs alone resulted in primarily a CD4 + response ( 99 ). It was only upon the SLP being bound to the liposome did the vaccine produce a strong CD8 + response, albeit at the slight expense of CD4 + activity ( 99 ).…”
Section: Peptide Vaccine Formulation and Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation